A Descriptive Correlational Study to Assess the Level and Physical Effects of Nomophobia Among College Students in Selected Colleges, Madurai - C, Ponnaruvi.; Raghavendran, M.; vedanayagi, V. Jesinda; cathrine R, Thephilah (Journal of Neonatal Surgery, 2025)
Technology has become a part and part of our life in recent years especially the smartphone, which has become handy and attractive as stated, technology is a boon but sometimes a curse, still a concealed fact. Nomophobia is a psychological condition were individual has a fear of getting disconnected from smartphone. This study is aimed to discover the nomophobia level among college students and its physical effects and also addresses the correlate between the level of nomophobia and its physical effects among college students. A descriptive correlation analysis was performed with a sample size of 103 nursing and diploma students selected by a convenient sampling technique. Data were collected using the Nomophobia Questionnaire and the Self-Structured Physical Effects Scale. The study findings discovered that 15 (14.6%) college students had a severe level of nomophobia, 55 (53.4%) had a moderate level of nomophobia, 31 (30.1%) had a mild level of nomophobia 2 (1.9%) had no nomophobia. Smartphones in turn cause considerable physical effects out of which pain, sleep Disturbance and insomnia contribute the highest percentage of 32 and 31% respectively. From this I conclude that , nomophobia is an emerging problem of concern among the younger generation the current study has shed light on the after effects of smartphone usage as the internet has popped up.